Hubungan Antara Dukungan Keluarga Dengan Kepatuhan Menjalani Hemodialisis Pada Pasien Gagal Ginjal Kronis - Uun Suyono (Media Husada Journal Of Nursing Science, 2026)
Abstract Hemodialysis therapy is one of the main efforts to maintain bodily function and quality of life in patients of Chronic Kiney Disease (CKD). However, the success of this therapy s highly dependent on the level of patient compliance, which s nfluenced by various factors, especially family support.This study aims to analyze the relationship between family supportand hemodialysis compliance n CKD patients undergoing therapy at the Hemodialysis Ward, Dr. Saiful Anwar Regional General Hospital, East Java. The0research designused was an analytical observational study with across-sectional approach and quantitative methods. The sample consisted of 58 adult patientsundergoing hemodialysis twice a week for 0–12 months, selectedusing purposive sampling. Data were collected using a structured questionnairecovering aspects of family support (emotional, nstrumental, andinformational) and hemodialysis adherence (frequency of attendance,diet compliance, medication management, and lifestyle). Analysis used Spearman's rank correlation testwith a significance level of a = 0.05. The results showed a significant positive correlation between family support and hemodialysis compliance (p <0.05). This study emphasizes the mportance of active family nvolvementin CKD  management through health education and psychosocial supportto improve the effectiveness of therapy and the quality of life of patients.